Sistem Penunjang Keputusan Penilaian Kelayakan Usaha Baru Menggunakan Metode Promethee - Pomada, Erick Putra (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2016)
Many entrepreneurs failed in his attempt because it does not prepare or do not know whether the effort is worth it or not to run. This leads to a lot of people are reluctant to invest capital in entrepreneurship because of fear for businesses that are not feasible or are not profitable. The result of this research is a decision support system using PROMETHEE to assess the feasibility of a new venture. This research is not just help to assess the feasibility of new businesses but also help in the making of business plan and projected financial statement of new venture.Keywords: PROMETHEE, Feasibility Study, Projected Financial Statement, Business Plan.